Biomechanical assessment of vertebrae with lytic metastases with subject-specific finite element models - Costa, M.C.; Eltes, P.; Lazary, A.; Varga, P.P.; Viceconti, M.; Dall’Ara, E. (Journal of the mechanical behavior of biomedical materials, 2019)
The assessment of risk of vertebral fracture in patients with lytic metastases is challenging, due to the complexity in modelling the mechanical properties of this heterogeneous material. Currently clinical assessment of patients at high risk of fracture is based on the Spinal Instability Neoplastic Score (SINS), which however in many cases does not provide clear guidelines. The goal of this study was to develop a computational approach to provide a comparative biomechanical assessment of vertebrae with lytic lesions with respect to the adjacent controls and highlight the critical vertebrae. The computed tomography images of the thoracolumbar spine of eight patients suffering of vertebral lytic metastases with SINS between 7 and 12 (indeterminate unstable) were analysed. For each patient one or two vertebrae with lytic lesions were modelled and the closest vertebrae without lesions were considered as control. Metastatic vertebrae (N = 12) and controls (N = 18) were converted to subject-specific, heterogeneous, isotropic, nonlinear finite element models for simulating uniaxial compression. Densitometric and mechanical properties were computed for each vertebra. In average, similar mechanical properties were found for vertebrae with lytic lesions and controls (e.g. ultimate force equal to 6.2 ± 2.7 kN for vertebrae with lytic lesions and to 6.2 ± 3.0 kN for control vertebrae). Only in three patients the vertebrae with lytic lesions were found to be mechanically weaker (−19% to −75% difference for ultimate stress) than the controls. In conclusion, in this study we presented an approach to estimate the mechanical competence of vertebrae with lytic metastases. It remains to be investigated in a clinical study if this method, together with the SINS, can better classify patients with vertebrae with lytic lesions at high risk of fracture. [Display omitted] •The biomechanical stability of metastatic vertebrae has been assessed.•Computed tomography based subject specific finite element models have been used.•This approach estimates the mechanical competence of metastatic vertebrae.•Vertebrae with lytic lesions may be critical or not for different patients.•The results have been integrated into a reporting mechanisms for clinicians.